Ground Zero Revisited – Museums and Materiality in an Age of Global Pandemic - Balfour, Lindsay Anne (Museum and Society, 2020)
This paper examines the potential of convergence technologies in the process of 9/11 memorialization, particularly when materiality and its absence are so crucial to the in-situ narrative of post terror attack. Questions over the incorporation of virtual and digital media are not new in the context of COVID-19 but are perhaps more urgent than ever, as we all begin to grapple with the turn to technology as a surrogate for what we cannot physically provide. In particular, I trace the Derridean phenomenon of autoimmunity to draw parallels between memorial practices associated with both 9/11 and COVID-19. Ultimately, the migration online initiated by global pandemic reminds us that traumatic memory in particular is punctuated by gaps and absences; it insists on the recognition of other, stranger, incomplete and imperfect ways of knowing and commemorating.